Development of a Multi-Platform Vehicle Rental Service Application using Research and Development (R&D) Methods - Erlangga Erlangga; Adam Sekti Aji (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Vehicle rental services still face various obstacles such as limited accessibility, manual management, and the absence of an integrated system. This study aims to develop a multi-platform web and mobile-based application model that can improve the efficiency and transparency of vehicle rental services. The research method used is Research and Development (R&D) with stages of needs analysis, system design, implementation, and testing using the System Usability Scale (SUS). Research data was obtained from direct interviews with rental owners and surveys of 21 potential users. The test results showed an average usability score of 79.4 out of 100, which is in the “good” category. This indicates that the developed application model is superior to the previous models (SDLC and RAD), which were only tested through black-box testing without measuring user usability. With these results, the research successfully introduced an R&D-based application development model that is measurable through SUS, thereby contributing scientifically to improving the effectiveness of the digital vehicle rental system.